PEMBERDAYAAN MASYARAKAT MELALUI DIVERSIFIKASI PRODUK PANGAN LOKAL BERBASIS BIJI JAWAK (SETARIA ITALICA) UNTUK PENCEGAHAN STUNTING DAN UPAYA PENGUATAN EKONOMI MASYARAKAT DESA JERORA SATU KABUPATEN SINTANG - Sunarti; Uray B. Asnol; Ria Damayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2025)
Sintang Regency is classified as a disadvantaged area with an extreme poverty status in Indonesia, and is one of the priority regions targeted in the National Action Plan for the Acceleration of Development in Disadvantaged Areas. Jerora Satu Village is one of the 29 villages in Sintang District, Sintang Regency, West Kalimantan. Sintang Regency is one of the regencies that directly borders a neighboring country, namely Malaysia, specifically the Sarawak region. The natural resource potential of Jerora Satu Village includes plantations and horticultural agriculture. One of the leading commodities originating from Jerora Satu Village is jawak (Setaria italica) and sweet corn. Jawak has strong potential as an alternative food crop, considering its nutritional content and its ability to grow in dry–climate areas. The nutritional content of jawak is three to five times higher than that of rice and wheat. The majority of residents rely on the agricultural, plantation, or fisheries sectors for their livelihoods. However, household income remains low due to limited technological support for diversified economic development and restricted access to wider markets. In addition, health problems such as stunting among toddlers have been identified; out of 108 toddlers, 20 (20.37%) were found to be stunted. Based on these issues, the proposed community empowerment program by BEM is titled: